Analisis Strategi Pengelolaan Keuangan dan Strategi Keberlanjutan Usaha Kerajinan Genteng Pejaten di Masa Pandemi Covid-19 (Studi Kasus di UD. Surya Indah, Desa Pejaten, Tabanan) - Gusti Ayu Triana Indra Lestari; Rencana Sari Dewi (Universitas Pendidikan Ganesha, 2021)
This research aims to analyze financial management strategies and strategies for the sustainability of the Pejaten tile craft business during the covid-19 period at UD. Surya Indah, Pejaten Village, Tabanan. This research uses a qualitative approach and will describe the research method, namely research case studies. Sources of data in this study are primary data and secondary data. The data obtained were then analyzed by data analysis techniques, namely data collection, data reduction, data presentation and drawing conclusions. The results of this study state that (1) the financial management strategy at UD. Surya Indah uses a petty cash system with a fluctuating method (2) the management system is not yet effective in controlling the company's financial management, therefore researchers contribute to assisting in the preparation of SAK EMKM, (3) efforts made by UD. Surya Indah to be able to maintain its business by paying attention to aspects of capital planning, raw material production process, marketing and customers, technology used, workforce owned, and forward looking.Keywords: Financial Management Strategy, Sustainability Strategya